Human resource practices that influence turnover intention among Generation Y employees in Bank Rakyat / Siti Nur Izyan Azlin - Azlin, Siti Nur Izyan (Faculty of Business and Management, 2020)
Turnover intention has been a major discussion among researchers and academicians. Most companies believe that turnover issue is a main concern because, employee turnover is a costly expense especially in lower paying job roles, for which the employee turnover rate is higher. Many factors play a role in the employee turnover rate of any company, and these can shoot from both the employer and the employees. In addition, today’s workforce is made up of different generations and each generation has its own characteristics, attitudes and behaviours toward their current or past jobs. It is crucial to study about each generation turnover intention as previous study have revealed that generation Y has the highest turnover rate. Hence, this research paper aimed to investigate factors that may influence turnover intention among generation Y employees in Bank Rakyat. Generation Y employees were selected as targeted population and the sample is 313. Convenience sampling technique was used for this project-paper and the distribution of survey was made via online. The instrument applied for this research was four-point Likert scale to help collecting data from the respondents. However, based on the findings, it was found that all human resources practices (training and development, compensation and organization culture) have negative relationship with turnover intention among generation Y employees in Bank Rakyat.